Philosophy and Teachers - Theodor W. Adorno (Філософія освіти, 2018)
Teodor Adorno's work Philosophy and Teachers was first read as a report at the Frankfurt Studenthome in November 1961. In this report Adorno continued the topic of criticism of those factors of the then formation of West Germany, which made impossible a personal fight intellectual to with the cultural remnants of a totalitarian society. Adorno drew attention an exam in philosophy, important element of the educational process. This exam should pass composed of future teachers, candidates for the work of the teacher of gymnasium. This exam should be composed by future teachers, candidates for the work of the teacher of gymnasium. Adorno noticed the tendency of formalistic adherence to the Rules of Examination by some future teachers who are unable to understand the humanistic, emancipatory and spiritual essence of philosophy, and therefore do not understand the purpose of conducting this exam. Adorno honored the long tradition of academic freedom of the German University and noticed the figure of the German philosopher, describing him as the man whose intellectual activity influenced the humanization of the German University,  which directly influenced to the corresponding cultural transformations. But in post-war universities in the Federal Republic of Germany there is a trend to the principles of scientific knowledge. This tendency is coupled with the attitude of some future teachers to knowledge as appropriation to the consumer way, was due to the absence of personal love for their own specialty and to their students. Adorno was convinced that such teachers are indifferent to their specialty and do not have a calling to him. Adorno defined as a sign to the absence of calling in these people is intellectual negligence, provincial speech and provincial inability to understand human freedom as a spiritual value. Such teachers are incapable of offering new knowledge to their students by way of perfekt speech and by way of perfekt written presentation. As completely different Adorno offered to see a person who is capable to appropriation of the knowledge that is needed to understand hemseif and his professional obligation. This person can will use self-understand and self-reflection, and therefore she can will independently to understand of the sense of their pedagogical work. This person will be faithful and patient in carrying out his work for the practical introduction of humanistic ideals of prior philosophical knowledge into society.